A novel function for platelet-derived growth factor D: induction of osteoclastic differentiation for intraosseous tumor growth - Huang, W (Nature Publishing Group, 2012)
Although increasing evidence suggests a critical role for platelet-derived growth factor (PDGF) receptor β (β-PDGFR) signaling in prostate cancer (PCa) progression, the precise roles of β-PDGFR and PDGF isoform-specific cell signaling have not been delineated. Recently, we identified the PDGF-D isoform as a ligand for β-PDGFR in PCa and showed that PDGF-D is activated by serine protease-mediated proteolytic removal of the CUB domain in a two-step process, yielding first a hemidimer (HD) and then a growth factor domain dimer. Herein, we demonstrate that the expression of PDGF-D in human PCa LNCaP cells leads to enhanced bone tumor growth and bone responses in immunodeficient mice. Histopathological analyses of bone tumors generated by PDGF-D-expressing LNCaP cells (LNCaP-PDGF-D) revealed osteolytic and osteoblastic responses similar to those observed in human PCa bone metastases. Importantly, we discovered a novel function of PDGF-D in the regulation of osteoclast differentiation, independent of the RANKL/RANK signaling axis. Although both PDGF-B and -D were able to activate β-PDGFR, only PDGF-D was able to induce osteoclastic differentiation in vitro, and upregulate the expression and nuclear translocation of nuclear factor of activated T cells 1, a master transcription factor for osteoclastogenesis. Taken together, these results reveal a new function of PDGF-D as a regulator of osteoclastic differentiation, an activity critical for the establishment of skeletal metastatic deposit in PCa patients.